The library needs of the students of Worldlab School (WLS), a school for dyslexia - Cuadra, Rajnna G. 1977- (2003)
Dyslexic librarianship is one area that needs to be addressed. This study aimed to find out what particular information dyslexics need and what they like to do most in the library, and what particular material they need most and how they want their library to be. The study used the structured question technique for its questionnaire that was administered to 45 students of Wordlab School from grades 2-6. Simple statistical methods were used to analyze the data. It was found that most dyslexics visit the library to read more than to borrow books. Many are aware of the library services and activities but a large number still rarely visit it for several reasons such as they are still unsatisfied with the information they get from the library. It would be very helpful for them to be assisted by a librarian in searching for books. They also request for a computer terminal and a wider variety of books to be added to the collection as well as to experience using a library card.
Vita.
Undergraduate thesis (B.L.I.S.)--University of the Philippines, Diliman.
Keywords: Special libraries -- Philippines -- Quezon City; Dyslexic children -- Services for -- Philippines -- Quezon City; Reading disability -- Philippines -- Quezon City